Hedge funds, exchange rates and causality: evidence from Thailand and Malaysia - Wan Ngah, Wan Azman Saini; Lau, Evan Poh Hock; Abdul Karim, Zulkefly (Routledge, 2010)
This article contributes to the debate on hedge funds and exchange rates in Thailand and Malaysia. It provides the first empirical evidence on causal relation between hedge funds and exchange rates. Using a new Granger noncausality procedure proposed by Toda and Yamamoto (1995) and monthly data for the January 1994 to April 2002 period, two important findings emerge. First, hedge funds lead Thai baht during the 1997 crisis. Second, there is a bidirectional causality between hedge funds and Malaysian ringgit for the pre-crisis period. In all other cases, no causal relation can be established.